Case Report: Long-term improvement after acupotomy in advanced ankylosing spondylitis with sacroiliac joint fusion - Chen, Yu; Ye, Zixi; Yuan, Yangguang; Cui, Xiangrui; Guo, Dongyue; Zhang, Liyong; Ding, Qiuxia (Frontiers in Surgery, 2025)
BackgroundEvidence for acupotomy in managing advanced ankylosing spondylitis (AS) with extensive bony fusion, particularly in treatment-refractory cases, remains limited. This report details its application and outcomes in one such patient.Case presentationA 27-year-old male with advanced, active AS and bilateral sacroiliac joint fusion presented with severe low back pain, kyphosis, and markedly restricted mobility. His condition was refractory to prior conservative therapies, including NSAIDs and traditional acupuncture. He subsequently underwent five sessions of anatomy-guided acupotomy, targeting fascial adhesions in the thoracolumbar fascia, sacroiliac ligaments, and lumbar facet joints.ResultsThe intervention yielded substantial and sustained improvements. Pain intensity (VAS) decreased from 7 to 2, while disease activity (BASDAI) and functional impairment (BASFI) scores reduced from 3.7 to 1.3 and 4.0 to 1.0, respectively. Spinal range of motion and postural alignment were largely restored. These functional benefits proved durable over a 2-year follow-up, during which follow-up imaging confirmed persistent structural fusion, underscoring that clinical improvement was attributable to restored soft-tissue function rather than structural reversal.ConclusionAcupotomy induced significant, long-term clinical improvement in this refractory AS case, likely through mechanical release of fascial restrictions. It represents a promising complementary, symptom- and function-modifying intervention for patients with limited response to conventional regimens.